Assessment and Calculation of Groundwater Reserves for Drinking Water Supply in Mountainous Areas of the Chechen Republic - Zaurbekov, Sh Sh; Ozdoyeva, L I; Shaipov, A A; Gridin, V A; Dzharnagaliyev, R Z; Movlayeva, A M; Sarkisyan, I V; Gadayeva, Z I (KnE Life Sciences, 2019)
This article is devoted to the urgent problem of drinking water supply in the mountainous regions of the Chechen Republic. The results of the assessment and calculation of groundwater reserves are presented. The article gives a brief assessment of the hydrogeological conditions of the study area, especially the complex of alluvial lower-upper Pleistocene sediments of the overdeepened river valleys, represented by boulder-pebble and boulder-rubbly formations with sand and sand-loamy aggregates. For inventory assessment and choice of a methodology of the reserves calculation in the Research Methods section, the hydrogeological conditions for the formation of groundwater are schematized in all the four study areas (Khimoyskiy, Shatoyskiy, Itum-Kalinskiy, Vedenskiy). On the basis of experimental field hydrogeological works, the calculation hydrogeological parameters necessary for the calculation of the groundwater reserves are determined (the main hydrogeological parameters on the estimated areas are given in the article, in the table 1). In the Methods section, the detailed justification of the scheme of placement of project wells is given (further the wells are supposed to be used as a water intake). For all the four areas – Khimoyskiy, Shatoyskiy, Itum-Kalinskiy and Vedenskiy the “strip aquifer” scheme is adopted as the calculation, limited by two parallel impermeable contours (the slopes of river valleys are composed of impermeable water-resistant bedrocks). In the Results section, all schemes, formulas and brief characteristics of each investigated area (the acreage, the necessary water demand, the type of project water intake) are given. For each area, an security assessment of the calculated reserves is given, which is confirmed by the balance method (all the calculations are given in the article). In conclusion of the article in table 03 the data on the reserves of fresh groundwater based on the results of prospecting-evaluation works of 01.06.2015 are given.